Hubungan Kepatuhan Terapi Kelasi Dengan Kadar Feritin Serum Pada Pasien Thalasemia B Mayorpada Anak Di Rsam Provinsi Lampung - Zulhafis Mandala; Festy Lady; Muhammad Fahrin Ramadhan (Universitas Malahayati, 2021)
ABSTRACT: RELATIONSHIP OF COMPLIANCE WITH KELSI THERAPY WITH SERUM FERITIN LEVELS IN THALASSEMIA β MAYOR PATIENTS IN CHILDREN AT BANDAR LAMPUNG HOSPITAL Background: Thalassemia is a heterogeneous group of hereditary anemia caused by mutations in hemoglobin synthesis (Cunningham et al., 2009). In the world, thalassemia annually reaches 1 in 100,000 people. The incidence of thalassemia in the world is based on data from the World Health Organization or the World Health OrganizationPurpose To determine the relationship between chelation therapy provision and serum ferritin levels in Thalassemia B Mayor patients in Dr. Hi Abdul Moeloek, Lampung Province in 2019.Aim: To find out the relationship between the adherence to iron therapy with serum ferritin levels at RSAM in 2019.Methods: This research is quantitative with the observational analytic method with a cross-sectional approach. The total population was 115 patients. A sample of 60 patients thalassemia β mayor. This research was conducted from Feb 2020 to completion. Analysis through univariate analysis.Results: the relationship of compliance with kelasi therapy with serum feritin levels in thalasemia β mayor patients at rsam hospital 2019, 34 respondents who obeyed chelation therapy, as many as 21 respondents (61.8%) had no risk ferritin levels (≤1000), of the 36 respondents who did not comply with chelation therapy, as many as 6 respondents (23.1%) had levels ferritin No Risk (≤1000) The results of the analysis also obtained an OR value of 5.38 (95% CI 1.7-16.9), which means that respondents who are adherent to iron therapy are at risk of having ferritin levels at risk (≥ = 1000) 5.38 times greater than who do not adhere to iron therapy.Conclusion: It is known that there is a relationship between adherence to iron therapy and serum ferritin levels at rsam hospital in 2019. Keywords: Thalassemia, Iron Therapy, Ferritin LevelsINTISARI: HUBUNGAN KEPATUHAN TERAPI KELASI DENGAN KADAR FERITIN SERUM PADA PASIEN THALASEMIA β MAYOR PADA ANAK DI RSAM BANDAR LAMPUNG Latar Belakang : Thalasemia merupakan salah satu kelompok heterogen anemia herediter yang disebabkan oleh mutasi pada sintesis hemoglobin (Cunningham et al., 2009). Di dunia, insiden thalasemia setiap tahunnya diperkirakan mencapai 1 dari 100.000 orang. Angka kejadian penyakit thalasemia di dunia berdasarkan data dari Badan Organisasi Kesehatan Dunia atau World Health OrganizationTujuan Mengetahui hubungan kepatuhan terapi kelasi dengan kadar feritin serum pada pasien Thalasemia B Mayor Di RSUD Dr. Hi Abdul Moeloek Provinsi Lampung Tahun 2019Metode Penelitian : Penelitian ini adalah kuantitatif dengan metode analitik observasional dengan pendekatan cross sectional. Jumlah populasi 115 pasien. Sampel 60 pasien dengan diagnosis thalassemia β mayor. Peneltian ini dilakukan pada bulan februari 2020 sampai dengan selesai. Analisa melalui analisa bivariat. Hasil : hubungan kepatuhan terapi kelasi dengan kadar ferritin serum pada pasien thalsemia β mayor di RSAM bandar lampung tahun 2019 34 responden yang patuh dalam terhadap terapi kelasi, sebanyak 21 responden (61,8%) memiliki kadar ferritin Tidak Beresiko (≤1000), dari 36 responden yang tidak patuh dalam terhadap terapi kelasi, sebanyak 6 responden (23,1%) memiliki kadar ferritin Tidak Beresiko (≤1000. Hasil analisis diperoleh pula nilai OR 5,38 (95% CI 1,7-16,9) yang berarti bahwa responden yang patuh dalam terhadap terapi kelasi, berisiko memiliki kadar feritin beresiko (≥=1000) 5,38 kali lebih besar dibandingkan dengan yang tidak patuh dalam terhadap terapi kelasi.Kesimpulan : Diketahui terdapat hubungan kepatuhan terapi kelasi dengan kadar ferritin serum di RSAM Bandar Lampung tahun 2020 Kata kunci : Thalasemia, Terapi Kelasi, Feritin Serum